ACADEMIC STRESS COPING STRATEGIES AMONG STUDENTS OF THE FACULTY OF FOREIGN LANGUAGES, THANG LONG UNIVERSITY, HANOI, ACADEMIC YEAR 2021–2022 (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the coping strategies for academic stress among students of the Faculty of Foreign Languages at Thang Long University during the 2021–2022 academic year.Methods: A cross-sectional descriptive study was conducted on students from the Faculty of Foreign Languages at Thang Long University. The Academic Coping Strategies Scale (ACSS) was used to assess students’ responses to stress, consisting of three categories: approach strategies, avoidance strategies, and social support. Higher scores indicate greater use of the respective coping strategy.Results: A total of 452 students participated in the study, with the majority being female (80.7%) and an average age of 19.4. The average total ACSS score was 101.59 ± 10.45 (range 34 to 170); specifically, the mean score for approach strategies was 51.29 ± 6.84 (range 15 to 75), avoidance strategies 27.15 ± 6.02 (range 11 to 55), and social support strategies 23.15 ± 4.78 (range 8 to 40).Conclusion: Students of the Faculty of Foreign Languages at Thang Long University predominantly employed approach (active) coping strategies in response to academic stress, while avoidance and social support strategies were used to a lesser extent.
Keywords: Stress, students, Thang Long University.